Thermal and mechanical properties of ferroelastic RENbO4 (RE = Nd, Sm, Gd, Dy, Er, Yb) for thermal barrier coatings. (15th April 2020) - Zhang, Peng; Feng, Yingjie; Li, Yi; Pan, Wei; Zong, Peng-an; Huang, Muzhang; Han, Yi; Yang, Zesheng; Chen, Hao; Gong, Qianming; Wan, Chunlei
Abstract: A new series of rare-earth niobates (RENbO4 ) are synthesized and investigated for potential thermal barrier coating (TBC) application. The thermal conductivities of RENbO4 are much lower than yttria stabilized zirconia (YSZ) mainly due to the chemical inhomogeneity. The lattice distortion contributes to the higher coefficients of thermal expansion (CTEs, 12.8 × 10 −6  K −1 ) of RENbO4 below the critical temperature. Especially, RENbO4 exhibits high fracture toughness (1.93–2.77 MPa m 0.5 ) comparable to YSZ, owning to the absorption of crack energy by the ferroelastic domain switching. The excellent thermal and mechanical properties give RENbO4 great potential as new durable TBC materials. Graphical abstract: Image, graphical abstract